Workplace Spirituality, Grit and Work Engagement. (March 2018) - Singh, Jasmeet; Chopra, Vandana Gambhir
Workplace spirituality and grit are gaining momentum among researchers, academicians and business professionals. While workplace spirituality is an extrinsic factor which refers to a supportive working environment, grit is an internal factor which refers to passion and perseverance. The aim of this article is to examine the impact of workplace spirituality and grit on work engagement. Data were collected using standardised questionnaires from 275 full-time employees working in various government, private and public–private organisations in Delhi-NCR, India. Correlational analysis showed a positive correlation between components of workplace spirituality (inner life, meaningful work and community) and components of work engagement (attention and absorption) and between components of grit (consistency of interest and perseverance) and components of work engagement (attention and absorption). Hierarchical multiple regression analysis showed that meaningful work, consistency of interest and perseverance significantly predicted work engagement after controlling for gender, age, tenure and educational qualification. This implies that organisations should hire employees with high grit and provide them with meaningful work to enhance their engagement. Practical and theoretical implications, along with the limitations of the study, are discussed.